Kerangka Evaluasi Pilkada : Evaluasi Pilkada Serentak Melalui Kerangka Integritas Pemilu - Rafif Pamenang Imawan (Badan Pengawas Pemilihan Umum, 2020)
The implementation of simultaneous local elections has been carried out since the 2015 elections. The purpose of the simultaneous local elections is to encourage the formation of strong government. This is based on the assumption that voters will elect their representatives in the executive and legislative branches at once. It is expected that this election design will encourage consolidation between the two representative rooms. Strong consolidation will encourage effective governance and policy making processes. This paper would like to provide an evaluation framework for the simultaneous election implementation from the electoral integrity dimension. It is important to consider the aspect of electoral integrity since the regulated procedures need to be connected with substantial justice in the election. The absence of the consideration of this aspect will lead to the problems of political dynasty, money politics, and violence threat in the implementation of election. This paper attempts to create a framework for evaluating simultaneous regional elections by using the concept of electoral integrity. Elaboration is made on the conception of electoral integrity with adjustments to local political problems in Indonesia. The data in this paper are sourced from journals, reports, and analysis related to the evaluation of simultaneous local elections. This paper shows that there are two important elements which need to be included from the global indicator in relation with electoral integrity, namely: the community participation and money politics, in order to review and evaluate the local election. The contribution of this paper is enriching studies related to the evaluation of elections at the local level, where the dominance of studies in local elections is on issues such as money politics, political dynasties, to the neutrality of ASN. Many of these local political problems have not been framed in a single election evaluation frame. This paper attempts to frame the dynamics of local politics with an evaluative framework adapted from the concept of elections with integrity contextualized to the dynamics of local elections.